PENGARUH BELANJA PEMERINTAH BIDANG PENDIDIKAN DAN BIDANG KESEHATAN TERHADAP PERTUMBUHAN EKONOMI MELALUI INDEKS PEMBANGUNAN GENDER KABUPATEN/KOTA dI PROVINSI JAMBI - Erisa Ifatul Azizah; Heriberta; Hardiani (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze: (1) to analyze the dynamics of education expenditure, health expenditure, economic growth, and gender development index of regencies/cities in Jambi Province in 2019-2023. (2) to analyze the influence of education expenditure and health expenditure on the gender development index of regencies/cities in the Province in 2019-2023. (3) the influence of education expenditure and health expenditure on economic growth through the gender development index of regencies/cities in Jambi Province in 2019-2023. The analytical method applied in this study is panel data path analysis. The results of the study show that: 1) the average development of education expenditure realization for the 2019-2023 period is 0.02 percent. The average development of health expenditure realization for the 2019-2023 period is 7.20 percent. The average economic development for the 2019-2023 period is 0.01 points. The average development of the GDI for the 2019-2023 period was 0.18 points. 2) Education spending and health spending did not have a simultaneous effect on the GPI of districts/cities in Jambi Province, while partially, education spending did not have a significant direct effect on the GDI, and health spending had a significant direct effect on the GDI. 3) Education spending, health spending, and GDI have a simultaneous effect on the economic growth of regencies/cities in Jambi Province, while partially, education spending does not have a significant direct effect on economic growth, and health spending does not have a direct effect on economic growth. Meanwhile, based on the Sobel test, education spending does not have a significant indirect effect on economic growth through the GDI, and health spending does not have a significant indirect effect on economic growth through the GDI.